The impact of human capital remittances on economic growth in Syria - موسى , نرمين; لؤي صيوح , (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to review the concept of financial transfers, and the patterns of using remittances, as there are several patterns of using remittances within the economies of the receiving countries. These patterns differ from one country to another depending on the economic, living and social conditions and the systems and policies followed in each country. The researcher relied on the descriptive analytical approach to study the general foundations and concepts of the subject studied, and the standard study based on the E-VIEWS10 program to clarify the extent to which financial transfers of human capital contribute to economic growth in Syria during the period (2000-2019). The results concluded: There is a significant relationship between financial transfers of human capital and long-term economic growth in Syria during the period studied. Then many recommendations were presented, the most prominent of which are: developing databases and information on the various dimensions of migration, especially on financial flows of human capital, so that in-depth studies can be carried out that ultimately reach accurate results, and stimulating and encouraging remittances through optimal exploitation of migrants’ savings in banks in order to Investing it in financing local or regional projects.